The Difference Between Hedonic Imputation Indexes and Time Dummy Hedonic Indexes - Heravi, Saeed (IMF Working Papers; Working Paper ;, 2006)
Statistical offices try to match item models when measuring inflation between two periods. For product areas with a high turnover of differentiated models, however, the use of hedonic indexes is more appropriate since they include the prices and quantities of unmatched new and old models. The two main approaches to hedonic indexes are hedonic imputation (HI) indexes and dummy time hedonic (DTH) indexes. This study provides a formal analysis of the difference between the two approaches for alternative implementations of the Tornqvist "superlative" index. It shows why the results may differ and discusses the issue of choice between these approaches.